Crisis of the reforms, market power and mitigation in the Peruvian electricity market - Luyo Kuong, Jaime (2008)
In this essay a quick review of the crises of the reforms of the electricity sector in Latin America and particularly in Peru is carried out; the main factors of the same and the ineffectiveness of the Efficient Generation Law are identified, as well as the strong indications of market power. For the Peruvian electricity market –with predominant hydroelectric production and complete liberalization of the spot market– a Nash-Cournot intertemporal equilibrium model is presented, solved as a mixed complementarity problem, which allows a diagnosis of the existence of market power and the application of essential measures. for the adoption of regulatory policies. It also proposes transition measures to competition.